'But Private Notes for My Own Memory'? Parliamentary Diaries, Parliamentary History and the Politics of Information in Early Stuart England. (12th October 2020) - Baker, Philip
Abstract: Early modern parliamentary diaries are a standard source for historians, and have long been used as a supplement to the official journals in reconstructions of debates and business at Westminster. This article adopts a contrasting approach and examines what diaries – viewed as sources in their own right – reveal about parliament and its members, methods of contemporary note‐taking, and the circulation and readership of political information. It begins with a review of the evidence for why, how, and to what ends members kept parliamentary diaries, before exploring the extent of their dissemination in early Stuart England. While recent literature has emphasized the circulation of materials relating to Jacobean and especially Caroline parliaments during the early 17th century, the article recovers the existence of a simultaneous interest in the parliamentary proceedings of the Elizabethan era. At a time when the future of parliament seemed uncertain, it argues that the evident market for, and readership of, Elizabethan material reflects contemporaries' increasing recognition of parliament's significance within the English state and their changing attitudes towards parliamentary history. Moreover, while Elizabethan parliamentary diaries and journals seemingly reinforced memories of a past 'golden age' of parliamentary rule, the article contends that contemporaries' production, dissemination, and reading of that material was a conscious form of political action in response to the constitutional crisis of their day.